Boardgame Sebagai Media Edukasi Bagi Orang Tua Terhadap Perkembangan Motorik Anak Penyandang Autisme di Kota Palembang - Asnia; Halim, Bobby; Patriansah, Mukhsin (UNIVERSITAS INDO GLOBAL MANDIRI, 2024)
Autism is a developmental disorder that affects communication, social interaction, behavior and learning ability. Autism is caused by a combination of genetic and environmental factors. Autism symptoms generally begin to appear at the age of 1.5 to 3 years, with obvious physical and mental decline compared to individuals who do not have autism. In this case, the main problem is parental guidance which is very influential, such as the lack of knowledge or understanding of parents about how to improve the development or ability of their children. This has a very bad impact, because it only makes autistic children feel not understood and accepted as they are. To overcome the problems in the developmental disorders of autistic children, a solution was found, namely the therapy given to each child with autism will indeed be more effective if it involves the active role of parents. Therefore, it is necessary to design a Visual Communication Social Campaign on the Role of Parents towards the Motoric Development of Children with Autism in Palembang City. In the process of designing media, the design thinking method is used which includes empathize, define, ideate, prototype, and test. With this design, it is expected to be an educational platform, especially the role of parents that can improve the motoric development of children with autism in Palembang City.